Modelling Impotance Perfomance Analysis (IPA) to improve service quality in luxury hotel / Nor Atiqah Abdul Karim , Nur Shuhada Mohamad Radzi and Siti Mariah Mohd Basri - Mohd Basri, Siti Mariah; Abdul Karim, Nor Atiqah; Mohamad Radzi, Nur Shuhada (Faculty of Hotel and Tourism Management, 2015)
This study investigated the usage of Importance Performance Analysis (IPA) to improve service quality among guests of luxury hotels in Kuala Lumpur. Questionnaires were used to obtain the perceptions of importance and performance of service quality from luxury hotel guests. Nine items of service quality were identified as areas need to be improved by luxury hotels in Kuala Lumpur namely furnishings in the room, quality of service of the restaurant, quality of the restaurant foods, receiving confirmation of reservation, helpful and friendly staffs, timely service, the check in and check out process, first impression of the hotel and dealing with complaints. From this study, it provides an opportunity to recognize, in ranking order, features that are considered important by the guests staying in luxury hotels and able to identify the areas of divergence in hotel service quality.